Social Media’s Role in Shaping Political News Consumption in Nepal - Rupakheti, Basanta Kumar (NPRC Journal of Multidisciplinary Research, 2025)
Background: Social media has transformed political news consumption, particularly among urban youth in Kathmandu, Nepal, displacing traditional media (TV, newspapers). Platforms like Facebook, YouTube, and X facilitate real-time engagement but amplify risks of filter bubbles, echo chambers, misinformation, and declining trust in journalism. Nepal’s rapid internet growth (15% annually) intensifies these dynamics, yet rural areas remain reliant on traditional sources. Objective: This study investigates (a) how social media alters political news consumption patterns (frequency, platform preference, engagement) in Kathmandu, and (b) its relationship with public trust in news sources. Methods: A comprehensive literature review analyzed secondary data from academic journals, reports (e.g., Pew Research, NTA), and regional studies. Thematic synthesis identified trends and challenges, framed through Uses and Gratifications Theory, Media Dependency Theory, Social Cognitive Theory, and Social Responsibility Theory. Findings: Platform Dominance: Facebook, YouTube, and X are primary news sources for Kathmandu’s youth, valued for interactivity and real-time updates. Trust Challenges: Algorithmic personalization fosters echo chambers and exposure to unverified content, eroding trust in both social and traditional media. Traditional Media Coexistence: While social media use surges, traditional media (especially radio/TV) retains significance in rural Nepal despite urban decline. Theoretical Insights: UGT explains preference for social media’s convenience; Media Dependency and Social Cognitive theories highlight its influence on perceptions and behaviors; Social Responsibility Theory underscores the tension with journalistic standards. Risks: Rapid information sharing enables misinformation proliferation and political polarization, exacerbated by low digital literacy. Conclusion: Social media is the dominant vector for political news among Kathmandu’s youth, offering accessibility and engagement but significantly threatening information integrity through filter bubbles, misinformation, and diminished trust. Traditional media persists in rural contexts. Responsible platform design, media literacy initiatives, and adaptation by traditional outlets are critical to mitigate risks and support informed citizenship. Novelty: This study uniquely synthesizes the interplay of social media consumption, trust dynamics, and theoretical frameworks (UGT, Media Dependency, Social Cognitive, Social Responsibility) within the under-researched context of Nepal’s evolving media landscape, focusing explicitly on Kathmandu’s urban demographic.